Discontinuité et ouverture à Chypre : la mise en tourisme de la frontière - Jérôme Lageiste; François Moullé (Territoire en Mouvement)
In 1974, in a geopolitical context of extreme tension between Greece and Turkey (Mauss-Copeaux, 2011), the sudden establishment (Novosselof, Neisse, 2007) of the Buffer Zone split Cyprus into two parts, confining the Greek Cypriots to the south of the island and the Turkish Cypriots to the north. If the creation of borders establishes on both sides distance in proximity (Arbaret-Schulz, 2008), the Buffer Zone in Cyprus has also introduced hostility in humanity, truly pitting people against each other.Besides the constituent stigma from the implementation of the Buffer Zone such as the ghost tourist resort Varosha (Lageiste, 2011), the distinction coming from material and symbolic membership (Groupe frontière, 2004) has come into force and shape all along the border : ostentatious display of their respective national and cultural attributes - Greek flags versus Turkish flags, steeples versus minarets. This opposition of identities (Di Méo, 2001) continues to assert itself despite repeated conciliatory attempts from the European Union and the United Nations.Nevertheless, from 2003, the opening of breaches in this hitherto hermetic separation - 6 passages are open today - has raised a lot of interest among tourists always eager to experience otherness. Flows (Van Houtum, 2007) have taken shape and led to the development of tourism in the northern part of the island which had remained away from tourist interest since the separation. Some opportunistic agencies have picked up this border originality and used it as a really attractive tourist product : observation of the Buffer Zone in Famagusta, coastal cruising along the abandoned Varosha seafront, opening of shopping centres on both sides of the crossing point opened in the heart of Nicosia, a pedestrian street with western franchises on the Greek side and souks on the Turkish side. This debordering phenomenon (Scott, 2009) has been maintaining, if not strengthening some territorial opposition, while the staging that accompanies it has allowed its capitalizing.Thus, this unique development of tourism has led to a renewed functioning , offering an apparent fluidity through the tourist flows, and also designing a scenography of opposition, conflictuality and resentment.